Digital Government and Sustainable Development - castro, Conceição (2022)
Sustainable development is a concern and a challenge of modern societies, either in developing and developed countries. Good governance is crucial to managing efficiently all kind of resources, including natural resources, for the well-being of current and future generations. Digital transformation can be a key driver of changes in governments if they want to enhance transparency, accountability and efficiency. E-government facilitates integrated policies and public services to promote sustainable and inclusive economic growth, social development and environmental protection. E-government contributes to efficient resource management, and so can help to improve namely natural resource usage in the present to avoid damage to their usage in the future. The aim of this study is to analyse the impact of e-government on sustainable development. Using a logit model, for a sample of 103 countries in the period 2003–2018, the results suggest that e-government development is a positive determinant for a country to attain sustainable development, proxied by adjusted net savings, that embraces a country’s economic, social and environmental development. This study provides evidence that e-government increases the probability to attain sustainable development mostly in developing and transition economies. The results also suggest that economic growth and gross national income per capita are significant positive influences in sustainable development in the whole sample and that countries with lower age dependency and natural resource rents are more likely to have sustainable development. Developing e-government allows promoting sustainable development, particularly in developing and in transition economies.